The Influence of Composite Thickness with or without Fibers on Fracture Resistance of Direct Restorations in Endodontically Treated Teeth - Torabzadeh, Hassan; Ghassemi, Amir; Sanei, Masoud; Razmavar, Sara; Sheikh-Al-Eslamian, Seyedeh Mahsa (Iranian Endodontic Journal, 2014)
Introduction: This in vitro study evaluated the influence of composite thickness (with or without fiber reinforcement) on fracture resistance of direct restorations in endodontically treated teeth. Methods and Materials: Fifty-six intact human premolars were chosen and randomly divided into four groups (n=14). After preparation of a mesio-occluso-distal (MOD) cavities and cusp reduction, the teeth were endodontically treated. Subsequently, the samples were restored with composite resin using the following protocols: group 1; composite onlay with cusp coverage of 1.5 mm, group 2; composite onlay with cusp coverage of 2.5 mm, group 3; composite onlay (including resin-impregnated fiber) with cusp coverage of 1.5 mm and group 4; composite onlay (including resin-impregnated fiber) with cusp coverage of 2.5 mm. The fracture resistance of teeth in all test groups was calculated by subjecting them to a progressively increasing compressive axial force in the universal testing machine with the cross-head speed of 1 mm/min to the point of fracture. The data were analyzed using the Kruskal-Wallis test. Results: The mean fracture strengths and obtained standard error were 1263.85±74.03 N, 1330.26±128.01 N, 1344.92±64.40 N and 1312.54±75.63 N for groups 1 to 4, respectively. Statistical analysis revealed no significant difference between groups. Conclusion: Cusp coverage of 1.5 and 2.5 mm in MOD access cavities with or without insertion of resin impregnated fiber had similar fracture rates in the endodontically treated teeth.